Success Rate of Glaucoma Drainage Device Implantation in Kariadi General Hospital Semarang 2020-2022: Oral Presentation - Observational Study - Resident - Apriliana, Rina; Rachmi, Fifin L; Puspasari, Denti; Maharani, (Ophthalmologica Indonesiana, 2024)
Introduction & ObjectivesGlaucoma is a leading cause of irreversible blindness, and implantation of drainage devices is aneffective treatment option for patients with advanced glaucoma. The purpose of this study was toinvestigate success rate of glaucoma drainage devices implantation in Kariadi HospitalMethodsThis study was an observational analytic study with a retrospective design. All patients who receivedVirna implantation between January 2020 and December 2022 were included. Intraocular pressure(IOP) examination was performed at baseline and at the first day, seventh day, first month, and thirdmonth following surgery. The success rate was divided into three groups: complete success if IOPwas